Needs and opportunities for measuring rural women’s empowerment in Guatemala: Possible applications of a Women’s Empowerment Metric for National Statistical Systems (WEMNS) - Valiente, Regina; Heckert, Jessica; Paz, Florencia; Cabnal, Edwin (International Food Policy Research Institute, 2024)
Gender equality and the empowerment of women and girls is reflected across policy priorities at global and national levels. Sustainable Development Goal 5 (SDG 5) seeks to achieve gender equality and the empowerment of all women and girls. Moreover, the Government of Guatemala, through the Presi-dential Secretariat for Women (SEPREM), has supported these priorities through the National Policy for the Promotion and Comprehensive Development of Women and the Equality of Opportunities Plan 2008-2023, particularly under its Equitable Economic and Productive Development policy line, which gives the agenda a thematic focus on women’s economic empowerment. Both policy instruments are designed to guide public institutions in achieving the goals that have been set by the Council of Minis-ters of Women of Central America and the Dominican Republic (COMMCA). Economic empowerment is one of the main lines of policy action under the Regional Policy on Gender Equality and Equity of SICA (PRIEG/SICA). As such, women’s economic empowerment is being prioritized at the national level in Guatemala, and also at the regional level across Central America and the Dominican Republic.